2005
DOI: 10.1242/jeb.01371
|View full text |Cite
|
Sign up to set email alerts
|

Rats are able to navigate in virtual environments

Abstract: SUMMARY Virtual reality (VR) systems are useful tools that enable users to alter environmental settings and the location of landmarks in an accurate and fast way. Primates have been shown to be able to navigate in virtual environments. For rodents, however, all previous attempts to develop VR systems in which rats behave in the same way as in corresponding 3-D environments have failed. The question arises as to whether, in principle, rodents can be trained to navigate in a properly designed virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
192
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(193 citation statements)
references
References 19 publications
0
192
1
Order By: Relevance
“…In contrast, in two-dimensional random foraging in VR with or without pillars, the distal visual cues are not paired repeatedly with any other cue, leading to a lack of spatial selectivity. Contrary to our VR system and results, a recent study found that during twodimensional random foraging in a VR system allowing full, 360° body rotation 35,37 , hippocampal neurons showed intact spatial selectivity 37 . This result could arise solely from the presence of a larger range of vestibular cues, which were diminished in our study; however, this explanation is incompatible with the presence of spatial selectivity in our tasks involving systematic paths.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, in two-dimensional random foraging in VR with or without pillars, the distal visual cues are not paired repeatedly with any other cue, leading to a lack of spatial selectivity. Contrary to our VR system and results, a recent study found that during twodimensional random foraging in a VR system allowing full, 360° body rotation 35,37 , hippocampal neurons showed intact spatial selectivity 37 . This result could arise solely from the presence of a larger range of vestibular cues, which were diminished in our study; however, this explanation is incompatible with the presence of spatial selectivity in our tasks involving systematic paths.…”
contrasting
confidence: 99%
“…We measured hippocampal activity during a two-dimensional randomforaging task in RW and VR [35][36][37] with similar distal visual cues (Fig. 1a).…”
Section: Nature Of Spatial Selectivity Of Hippocampal Responsesmentioning
confidence: 99%
“…resent position. Another possibility is recordings in a virtual reality setting, where the available space for exploration is infinite (Holscher et al, 2005;Dombeck et al, 2007).…”
Section: Open Questionsmentioning
confidence: 99%
“…However, there is no agreement on which is more important and how these signals combine to generate spatially localized place cell firing and its temporal organization with respect to the theta rhythm (24). Recent studies showed that mice could navigate in a virtual environment (VE) and a small sample of place cells has been recorded in mice running on a virtual linear track (25)(26)(27). VE affords the opportunity to isolate the visual environment and internal movement-related information from other sensory information, and to study their contributions to place cell firing.…”
mentioning
confidence: 99%